A HUSBAND’S NEGLET OF MAINTENANCE OBLIGATION FOR HIS WORKING WIVES FROM AN ISLAMIC LAW PERSPECTIVE - Siti Maqfirah; Zaiyad Zubaidi; Faisal Yahya; Muhammad Ash Shiddiqi (Universitas Nurul Jadid, 2026)
Spousal support is a key component in building a harmonious household. However, when a wife earns an income through her work, husbands often become neglectful and assume that providing spousal support is no longer necessary. The purpose of this study is to examine the role of Islamic law in addressing the neglect of spousal support for working wives in Gampong Pulolhoih. This study employs a qualitative approach using a case study design. Data were collected through in-depth interviews, observation, and documentation. The data were then analyzed through data organization and descriptive analysis to describe the cases by linking them to explanatory analysis. The results of the study indicate that Islamic law, explicitly through its primary reference, the Qur’an, has addressed the husband’s obligation to fulfill his wife’s rights; even if the wife has her own income, this does not automatically nullify the husband’s obligation. Findings in Gampong Pulolhoih indicate that the issue of spousal support neglect is not a new one; this is evident from the procedures and steps that must be taken to address this matter. The process begins with resolving the issue through family deliberation, proceeds to the village level if no resolution is reached, and may ultimately end up in the legal system through the religious courts. The practice of neglecting spousal support for working wives in Gampong Pulolhoih is generally caused by the uncertainty of the husband’s employment and income, compounded by deeply ingrained bad habits in daily life.